Environmental and Health Impacts of Rice Milling: A Case Study of Dinajpur Sadar Upazila, Bangladesh - Md. Siam UL Hasan; Md. Ibrahim Hossain; Shahorare Ahomed; Selina Akhter; Abdullah-Al-Mamun; Md. Mostafizur Rahman (International Journal of Climate Conditions, 2025)
Rice milling plays a crucial role in Bangladesh's agricultural economy but contributes significantly to environmental pollution, affecting air, water, and soil quality, which in turn impacts public health and agricultural productivity. While prior studies have focused on immediate health effects like respiratory problems and reduced crop yields, they often overlook long-term consequences such as chronic diseases, soil degradation, and socio-economic impacts. Additionally, there is limited comparison between traditional and automated rice milling methods. Additionally, a lot of research uses self-reported data, which may be biased. This research fills these gaps by comprehensively assessing the environmental, agricultural, and health impacts of rice mill pollution in Dinajpur Sadar Upazila. It examines the effects of pollution on local communities, including their income, knowledge, and attitudes, and evaluates how proximity to rice mills influences crop productivity and health. Data was collected through surveys and interviews with residents, farmers, and health experts, and analyzed using statistical methods like linear regression. The findings reveal significant negative impacts on crop productivity and public health, particularly for those living within 500 meters of mills. The study calls for stronger environmental regulations, better waste management, and public awareness initiatives to mitigate pollution's effects, offering valuable insights for policymakers and planners in Bangladesh and similar areas.
Keywords: Dinajpur Sadar Upazila; Environmental impact; distance effect; human health; rice mill pollution